Clostridium difficile disease in solid organ transplant recipients: a recommended treatment paradigm. Issue 4 (August 2020) - Wong, Darren; Nanda, Neha
Abstract : Purpose of review: Organ transplant recipients have an increased incidence of Clostridium difficile disease and lower clinical response rates compared with the general population. Transplant specific treatment approaches are not defined. Therefore, a review of therapeutics in the transplant population is needed. Recent findings: A literature review on the current therapies for C. difficile was performed focusing on the evidence in transplant recipients and immunosuppressed populations. Summary: Transplant patients warrant an aggressive approach to treatment. The authors propose a suggested treatment paradigm for therapy.